Manajemen Layanan Khusus Ekstrakulikuler di SMP Science Quran Al Irsyad Al Islamiyyah Jember - Nur Lailatul Komariyah; Wafiq Fathurrohman; Azizatul Amaliyah Amaliyah; Rofiq Hidayat (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2023)
This research aims to describe the management functions of extracurricular activities at SMP Science Quran Al Irsyad Al Islamiyyah Jember, as well as to identify the supporting and inhibiting factors in the implementation of these activities. The study adopts a qualitative descriptive approach and is classified as field research. Data collection was conducted through structured interviews, documentation, and passive participant observation. The determination of research subjects was carried out using purposive sampling techniques, resulting in the selection of the deputy head of the school, the head of the school, and several students as respondents. To ensure the validity and reliability of the data, this study employed both source triangulation and methodological (engineering) triangulation techniques. The research findings indicate that SMP Science Quran Al Irsyad Al Islamiyyah Jember has implemented various extracurricular activity programs designed to develop and enhance students’ talents and interests. Each type of extracurricular activity is supported by a well-defined organizational structure and follows a systematic management process that includes planning, organizing, implementation, and evaluation stages. These activities not only serve as a medium for skill development but also contribute to building students’ character, discipline, and social responsibility within the school environment.